From the ground up: Experiential learning strengthens water governance - Meinzen-Dick, Ruth S.; Falk, Thomas; ElDidi, Hagar; Kosec, Katrina; Zhang, Wei; Carrillo, Lucia; Priyadarshini, Pratiti; Duche, Vishwambhar; Melesse, Mequanint B. (CGIAR System Organization, 2025)
After the final round of a groundwater learning game in a village in India, the buzz of discussion and decision-making among farmers settled into reflection during the post-game community debriefing meeting. One participant said to the game’s facilitators: “you have been coming here and telling us about sustainable management for a long time. But now we finally get it.”